2000
DOI: 10.1177/1541931200044028107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Clarity of Highway Entrance-Ramp Directional Signs

Abstract: Near the approaches of interstate and other major highways, posted directional signs warn drivers about the proper lanes for entering these high-speed limited-access roadways. These signs are intended to guide drivers with clear, concise directions, but they may instead expose drivers to ambiguous information. This ambiguity has the potential for causing accidents when the wrong lane is chosen and the driver must cross several lanes of traffic in these frequently busy interchanges. The present study exantined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Past research and theory indicates that the use of both text and pictures improves comprehension (Pavio, 1971). Improved comprehension of complete text and symbol coding extends to traffic signage (Barnes, Levine, and Wogalter, 2000). Previous research indicates that partial combinations of symbol and text may impede message comprehension (Morrow, Hier, Menard, & Leirer, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Past research and theory indicates that the use of both text and pictures improves comprehension (Pavio, 1971). Improved comprehension of complete text and symbol coding extends to traffic signage (Barnes, Levine, and Wogalter, 2000). Previous research indicates that partial combinations of symbol and text may impede message comprehension (Morrow, Hier, Menard, & Leirer, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Barnes, Levine and Wogalter (2000) examined interstate highway entrance-ramp direction signs. They found that two signs, one with an Arrow & Text, and one with Text-Only, were understood better than conventional Arrow-Only directional signs.…”
Section: Introductionmentioning
confidence: 99%
“…In examining the appropriate components of signs, several studies (Dewar, Ellis & Mundy, 1976;Kline, Buck, Sell, Bolan & Dewar, 1999;Kline, Ghali, Kline & Brown, 1990) have reported faster response times for signs with graphics (Symbols & Arrows), but a few studies report faster response times for Text-Only signs (Dewar, Ells, & Mundy, 1976;Shoptaugh & Whitker, 1984). Barnes, Levine and Wogalter (2000) examined interstate highway entrance-ramp direction signs. They found that two signs, one with an Arrow & Text, and one with Text-Only, were understood better than conventional Arrow-Only directional signs.…”
Section: Introductionmentioning
confidence: 99%